CONSTRUCTING PATIENT LOYALTY IN A COMPETITIVE ERA: THE CRITICAL ROLE OF BRAND AWARENESS IN PRIVATE HOSPITAL MARKETING STRATEGY - Lailatul Kodriyah; Vivina Maysella Damayanti; Ella Mayasari (Journal of Public Health Science, 2025)
Background: Competition in the healthcare industry compels private hospitals to build sustainable patient loyalty. Brand awareness is hypothesized to be a critical foundation in constructing this loyalty, particularly in shaping patients' proactive choices amidst numerous alternatives. Objective: This study aims to analyze the role of brand awareness in the marketing strategy of private hospitals by examining its relationship with outpatient loyalty. Method: This research employs a quantitative approach with a cross-sectional design. Seventy-seven outpatients from a type C private hospital in East Java were selected purposively. Data were collected using a questionnaire measuring the variables of brand awareness (through indicators of recognition, recall, and preference) and patient loyalty (through indicators of repurchase intention and recommendation). Data analysis used the Spearman's Rank correlation test. Results: The level of brand awareness was in the moderate category (54.5%), while patient loyalty was in the high category (57.1%). Statistical testing revealed a significant and strong positive relationship between the two variables (correlation coefficient = 0.683; p-value = 0.000). Conclusion: Brand awareness plays a critical role in constructing patient loyalty in private hospitals. These findings highlight that an integrated marketing strategy must prioritize enhancing brand awareness, particularly the aspect of brand recall (spontaneous memory), as a strategic step to build long-term loyalty and competitiveness in an intensely competitive era.